Musicians’ Online Performance during Auditory and Visual Statistical Learning Tasks - Mandikal Vasuki, Pragati R.; Sharma, Mridula; Ibrahim, Ronny K.; Arciuli, Joanne (Frontiers in Human Neuroscience, 2017)
Musicians’ brains are considered to be a functional model of neuroplasticity due to the structural and functional changes associated with long-term musical training. In this study, we examined implicit extraction of statistical regularities from a continuous stream of stimuli – statistical learning. We investigated whether long-term musical training is associated with better extraction of statistical cues in an auditory statistical learning (aSL) task and a visual statistical learning (vSL) task – both using the embedded triplet paradigm. Online measures, characterized by event related potentials, were recorded during a familiarization phase while participants were exposed to a continuous stream of individually presented pure tones in the aSL task or individually presented cartoon figures in the vSL task. Unbeknown to participants, the stream was composed of triplets. Behavioural data was also collected in the form of forced choice trials in a separate test phase (embedded triplets versus foil triplets) as another measure of statistical learning. Musicians showed advantages when compared to non-musicians in the online measure (early N1 and N400 triplet onset effects) as well as the behavioural measure (better scores) during the aSL task. However, there were no differences between musicians and non-musicians for behavioural and online measures for the vSL task. Results from the current study show that musical training is associated with enhancements in extraction of statistical cues only in the auditory domain.